PENGARUH MUTU PELAYANAN KEBIDANAN DAN KOMUNIKASI BIDAN TERHADAP KEPUASAN PASIEN DI IRNA C RSUD SYARIFAH AMBAMI RATO EBUH, BANGKALAN - Sri Indah Lestariani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2016)
The success of health care quality health service that can give satisfaction to every health care service users in accordance with the satisfaction level of the average - average population and communication is a very special process and means in human relations, especially in health care midwife. Midwife is one of the health workers have an important and strategic position in providing health services. Studies conducted in hospitals Syamrabu said that 53.3% of patients were less satisfied with the services of midwives.This research method uses a quantitative approach and the kind of research the correlation. The population is all inpatients in hospitals Syamrabu IRNA C. Techniques of collecting data using questionnaires. Data analysis using Chi Square test.The results showed that nearly all respondents say satisfied with the services and communication midwives in hospitals Syamrabu IRNA C Bangkalan. So that Ha received no influence quality of obstetric care and communication midwife the satisfaction of patients in hospitals SyamrabuBangkalan.With the results obtained then the hospitals must maintain and improve the services provided in hospitals Syamrabu particularly in the field of care that patients increasingly reliant on services in hospitals SyamrabuBangkalan and provide an opportunity for health workers to attend training - training seta up date scienceKeywords: Quality of Services, Communications Midwives, Patient Satisfaction